A large point-source outbreak of Salmonella Typhimurium linked to chicken, pork and salad rolls from a Vietnamese bakery in Sydney - Beth Cullen; Marianne Tegel; Rowena Boyd; Brett Campbell; Kirsty Hope; Stephen Conaty; Essi Huhtinen; Sophie Norton (Western Pacific Surveillance and Response, 2012)
Introduction: In January 2011, Sydney South West Public Health Unit was notified of a large number of people presenting with gastroenteritis over two days at a local hospital emergency department (ED).Methods: Case-finding was conducted through hospital EDs and general practitioners, which resulted in the notification of 154 possible cases, from which 83 outbreak cases were identified. Fifty-eight cases were interviewed about demographics, symptom profile and food histories. Stool samples were collected and submitted for analysis. An inspection was conducted at a Vietnamese bakery and food samples were collected and submitted for analysis. Further case ascertainment occurred to ensure control measures were successful.Results: Of the 58 interviewed cases, the symptom profile included diarrhoea (100%), fever (79.3%) and vomiting (89.7%). Salmonella Typhimurium multiple-locus-variable number tandem repeats analysis (MLVA) type 3-10-8-9-523 was identified in 95.9% (47/49) of stool samples. Cases reported consuming chicken, pork or salad rolls from a single Vietnamese bakery. Environmental swabs detected widespread contamination with Salmonella at the premises.Discussion: This was a large point-source outbreak associated with the consumption of Vietnamese-style pork, chicken and salad rolls. These foods have been responsible for significant outbreaks in the past. The typical ingredients of raw egg butter or mayonnaise and pate are often implicated, as are the food-handling practices in food outlets. This indicates the need for education in better food-handling practices, including the benefits of using safer products. Ongoing surveillance will monitor the success of new food regulations introduced in New South Wales during 2011 for improving food-handling practices and reducing foodborne illness.